Oral Health Status Among Children with Physical Disabilities: An Intervention Study - Mohamed, Samiyah; Hassan Hassan (AlQalam Journal of Medical and Applied Sciences, 2025)
Oral diseases are the most prevalent non-communicable diseases, especially caries and periodontal disease. Disabled children face higher risks, and an audiovisual educational aid improves parents’ and caregivers’ oral health. The main objective of the current study was to assess the oral health status in a group of disabled children, to determine the oral health knowledge levels of their parents, and to examine the impacts of a parental educational program in Benghazi, Libya. The study enrolled 250 children aged 6–16 years with orthopedic, visual, hearing, or speech disabilities (excluding intellectual disabilities and autism) and their parents from a Benghazi special needs health school. Initially, sociodemographic and oral‐health data were gathered via structured interviews and clinical assessments of gingival, plaque, and periodontal indices; parents then attended four interactive educational sessions on oral hygiene, diet, fluoride, sealants, and dental visits, after which both parental knowledge and children’s oral indices were reassessed three months later using the same methods. All data were entered into IBM SPSS v24, described in terms of numbers and percentages, and compared using chi-square tests. Regression analysis was then performed to identify the determinants of parental knowledge. Following the intervention, children demonstrated significant improvements in gingival, plaque, and periodontal disease index scores. Parents’ oral health knowledge also increased markedly, with male child gender, type of disability, parents’ education levels, and family income identified as key determinants of this knowledge gain. The newly implemented program, incorporating audio-visual materials designed to promote comprehensive oral health care, demonstrated a substantial increase in oral health awareness among the parents or guardians of individuals with intellectual disabilities.